2018
DOI: 10.1021/acschemneuro.8b00498
|View full text |Cite
|
Sign up to set email alerts
|

Role of Parkinson’s Disease-Linked Mutations and N-Terminal Acetylation on the Oligomerization of α-Synuclein Induced by 3,4-Dihydroxyphenylacetaldehyde

Abstract: Identifying the mechanisms by which the presynaptic protein α-synuclein (aSyn) is associated to neurodegeneration of dopamine neurons is a major priority in the Parkinson's disease (PD) field. Studies indicate that DOPAL (3,4-dihydroxyphenylacetaldehyde), an aldehyde generated from the enzymatic oxidation of dopamine, may convert aSyn monomer into a neurotoxin via formation of covalently stabilized toxic oligomers. Herein we investigated the role of N-terminal acetylation and familial aSyn mutations (A30P, A53… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 64 publications
0
46
0
Order By: Relevance
“…For mutated versions of a-Syn that are associated with early-onset PD (A30P, E46K, and A53T), the anti-aggregation effect of Nt acetylation becomes impaired, suggesting a cooperative link between the regions of these mutations and the N terminus (Ruzafa et al, 2017). PD specifically affects dopaminergic neurons, and a neurotoxic effect on a-Syn caused by DOPAL (3,4-dihydroxyphenylacetaldehyde), a biproduct in the synthesis of dopamine, has been investigated by Lima et al (2018), among others. Very recently, they found that wild-type Nt-acetylated a-Syn is less prone to form oligomers in the presence of DOPAL than non-Nt-acetylated a-Syn, whereas the opposite was found for inherited mutations of a-Syn (A53T, E46K, and H50Q) (Lima et al, 2018).…”
Section: Molecular Cellmentioning
confidence: 99%
See 1 more Smart Citation
“…For mutated versions of a-Syn that are associated with early-onset PD (A30P, E46K, and A53T), the anti-aggregation effect of Nt acetylation becomes impaired, suggesting a cooperative link between the regions of these mutations and the N terminus (Ruzafa et al, 2017). PD specifically affects dopaminergic neurons, and a neurotoxic effect on a-Syn caused by DOPAL (3,4-dihydroxyphenylacetaldehyde), a biproduct in the synthesis of dopamine, has been investigated by Lima et al (2018), among others. Very recently, they found that wild-type Nt-acetylated a-Syn is less prone to form oligomers in the presence of DOPAL than non-Nt-acetylated a-Syn, whereas the opposite was found for inherited mutations of a-Syn (A53T, E46K, and H50Q) (Lima et al, 2018).…”
Section: Molecular Cellmentioning
confidence: 99%
“…PD specifically affects dopaminergic neurons, and a neurotoxic effect on a-Syn caused by DOPAL (3,4-dihydroxyphenylacetaldehyde), a biproduct in the synthesis of dopamine, has been investigated by Lima et al (2018), among others. Very recently, they found that wild-type Nt-acetylated a-Syn is less prone to form oligomers in the presence of DOPAL than non-Nt-acetylated a-Syn, whereas the opposite was found for inherited mutations of a-Syn (A53T, E46K, and H50Q) (Lima et al, 2018).…”
Section: Molecular Cellmentioning
confidence: 99%
“…Although AcAS was capable of forming oligomers in the presence of DOPAL, the extent of oligomerization was significantly reduced. However, AcAS carrying the familial mutations A53T, E46K, or H50Q formed larger oligomers than WT AS (Lima et al ).…”
Section: Post‐translational Modifications Of α‐Synucleinmentioning
confidence: 99%
“…In a recent study, the effect of familial mutations on DOPAL induced oligomerization of AS was investigated (Lima et al ). 3,4‐dihydroxyphenylacetaldehyde (DOPAL), an aldehyde generated from the enzymatic oxidation of dopamine, causes the formation of AS oligomers.…”
Section: Post‐translational Modifications Of α‐Synucleinmentioning
confidence: 99%
“…3,4-Dihydroxyphenylacetaldehyde (DOPAL) is a catabolite generated from dopamine by monoamine oxidase (Burke et al, 2003; Goldstein et al, 2011). It has been shown that DOPAL can cause α-synuclein oligomerization in vitro and in cell models (Burke et al, 2008; Lima et al, 2018). Plotegher et al (2017) showed that this kind of α-synuclein-DOPAL oligomers can permeabilize cholesterol-containing lipid membranes mimicking SVs in vitro , which suggests that the synergistic effect of α-synuclein and DOPAL accumulation in DA neurons may lead to the formation of oligomers, negatively impacting the structure and function of SVs.…”
Section: Toxicity Of α-Synucleinmentioning
confidence: 99%